2013
DOI: 10.3892/ijo.2013.1913
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition triggers cancer stem cell generation in human thyroid cancer cells

Abstract: Abstract.Increasing evidence has shown that cancer stem cells or tumor initiating cells are the 'root cause' of malignant cancers. However, the exact origin of cancer stem cells still remains obscure in thyroid research. EMT has been implicated in the initiation and conversion of early-stage tumors into invasive malignancies and is associated with the stemness of cancer cells. Based on these facts, a new hypothesis was suggested that EMT induces cancer stem cell generation and tumor progression in human thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 37 publications
2
62
0
1
Order By: Relevance
“…Overexpression of HIF1a which increased the stem-like side population in this cell line. These results suggest that EMT induction promotes CSCs in thyroid tumors (Lan et al 2013).…”
Section: Emt and Cscsmentioning
confidence: 53%
See 1 more Smart Citation
“…Overexpression of HIF1a which increased the stem-like side population in this cell line. These results suggest that EMT induction promotes CSCs in thyroid tumors (Lan et al 2013).…”
Section: Emt and Cscsmentioning
confidence: 53%
“…Recent studies have revealed that the epigenetic silencing of E-cadherin is orchestrated by a variety of histone-modifying enzymes that cooperate to repress the CDH1 promoter (Tam & Weinberg 2013). Further understanding of the role of EMT and CSCs in cancer progression may reveal new therapeutic targets thyroid cancers (Lan et al 2013). …”
Section: Emt and Cscsmentioning
confidence: 99%
“…However, no consensus has been obtained on the location of adult pancreatic stem cells that give rise to b-cells, as conflicting in vivo data suggest that they are either present in the ductal, acinar, or islet compartment of the pancreas [8]. The occurrence of epithelial-mesenchymal transition (EMT) fits with the second theory on the origin of CSCs, and has been implicated to induce CSC generation and epithelial tumor progression [9,10]. EMT has also been implicated as a critical step in tumorigenesis of pNETs [11].…”
mentioning
confidence: 96%
“…Moreover, it was observed that cells with an over-expression of HIF1α shared stem-like cell features highlighting that EMT induction was directly associated with increased CSC populations. 84 Several lines of evidence also supported the cross-talk between Twist and ID proteins. Kebebew et al 93 observed over-expression of the DNA-binding protein inhibitor ID-1 in ATC tissues, reporting that the inhibition of ID1 mRNA expression results in decreased growth and reduction of Tg and NIS expression.…”
Section: Controlmentioning
confidence: 94%
“…[81][82][83] This model is supported by the expression of EMT markers in CSCs and by the activation of SC markers in EMT-induced cells. 84,85 DTCs are considered the major cause of metastatic disease, chemo-resistance and recurrence, and are characterised by the capacity to migrate from primary tumours to secondary sites. Therefore, DTCs can exist for long time in a quiescent state called dormancy, corresponding to the latent period between primary tumour detection, treatment, recurrence and metastatic spread.…”
Section: Thyroid Cscs and Metastasismentioning
confidence: 99%